2018
DOI: 10.1016/j.biopen.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

AhR signaling pathways and regulatory functions

Abstract: Animals and humans are exposed each day to a multitude of chemicals in the air, water and food. They have developed a battery of enzymes and transporters that facilitate the biotransformation and elimination of these compounds. Moreover, a majority of these enzymes and transporters are inducible due to the activation of xenobiotic receptors which act as transcription factors for the regulation of their target genes (such as xenobiotic metabolizing enzymes, see below §4 for the AhR). These receptors include sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
334
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 421 publications
(379 citation statements)
references
References 93 publications
(108 reference statements)
7
334
0
4
Order By: Relevance
“…This gene encodes a repressor of AHR, which has been previously associated with coffee consumption in a large-scale GWAS (n=91,462) 33 . AHRR and AHR, alongside with CYP1A1 and CYP1A2, belong to the xenobiotic metabolism pathway, in which AHR is activated via various ligands such as polycyclic aromatic hydrocarbons (PAHs) or with ligands of natural origins (e.g., food) 58 . PAHs are carcinogenic substances found in tobacco smoke 59 , which can also be formed during coffee roasting processes 60 .…”
Section: Discussionmentioning
confidence: 99%
“…This gene encodes a repressor of AHR, which has been previously associated with coffee consumption in a large-scale GWAS (n=91,462) 33 . AHRR and AHR, alongside with CYP1A1 and CYP1A2, belong to the xenobiotic metabolism pathway, in which AHR is activated via various ligands such as polycyclic aromatic hydrocarbons (PAHs) or with ligands of natural origins (e.g., food) 58 . PAHs are carcinogenic substances found in tobacco smoke 59 , which can also be formed during coffee roasting processes 60 .…”
Section: Discussionmentioning
confidence: 99%
“…As a ligand‐inducible transcription factor, AHR has been found to regulate the expression of a variety of genes involved in the metabolism of chemical compounds as well as in regulating cell proliferation, apoptosis, and tumor development . AHR also promotes Th17 and Treg differentiation and is essential for induction of IL‐22 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that AHR inhibited IL-17-mediated signaling via inactivation of P38 pathway and disruption of TAK1-MKK3/6 interaction, resulting in downregulated phosphorylation of MKK3/6 and suppressed IL-17 signaling. As a ligand-inducible transcription factor, AHR has been found to regulate the expression of a variety of genes involved in the metabolism of chemical compounds as well as in regulating cell proliferation, apoptosis, and tumor development [19][20][21][22]. AHR also promotes Th17 and Treg differentiation and is essential for induction of IL-22 [31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its role in xenobiotic metabolism, the AhR has physiologically relevant functions. Through multiple mechanisms, the versatile nuclear receptor AhR affects liver and vascular development, cell cycle progression, immune function and circadian rhythm (Jaeger, Khazaal et al., ; Larigot, Juricek, Dairou, & Coumoul, ). Genomic AhR signalling was elucidated experimentally using xenobiotic ligands (Figure a).…”
Section: Ahr Signallingmentioning
confidence: 99%
“…XAP2 and p23 maintain the stability of the hsp90 complex (Guyot, Chevallier, Barouki, & Coumoul, ). Conformational change following ligand binding exposes a nuclear localisation signal, which allows translocation of the AhR complex into the nucleus (Larigot et al., ). After the ligand is released, AhR heterodimerises with aryl hydrocarbon receptor nuclear translocator (ARNT) in the nucleus, which subsequently targets AhR:ARNT to specific xenobiotic response elements (XRE) in target gene promoters.…”
Section: Ahr Signallingmentioning
confidence: 99%